Evoked Compound Action Potentials Reveal Spinal Cord Dorsal Column Neuroanatomy. Issue 1 (19th June 2019) - Parker, John L.; Obradovic, Milan; Hesam Shariati, Nastaran; Gorman, Robert B.; Karantonis, Dean M.; Single, Peter S.; Laird‐Wah, James; Bickerstaff, Mark; Cousins, Michael J.
Abstract : Introduction: The electrically evoked compound action potential (ECAP) is a measure of the response from a population of fibers to an electrical stimulus. ECAPs can be assessed during spinal cord stimulation (SCS) to elucidate the relationship between stimulation, electrophysiological response, and neuromodulation. This has consequences for the design and programming of SCS devices. Methods: Sheep were implanted with linear epidural SCS leads. After a stimulating pulse, electrodes recorded ECAPs sequentially as they propagated orthodromically or antidromically. After filtering, amplification, and signal processing, ECAP amplitude and dispersion (width) was measured, and conduction velocity was calculated. Similar clinical data was also collected. A single‐neuron computer model that simulated large‐diameter sensory axons was used to explore and explain the observations. Results: ECAPs, both animal and human, have a triphasic structure, with P1, N1, and P2 peaks. Conduction velocity in sheep was 109 ms −1, which indicates that the underlying neural population includes fibers of up to 20 μm in diameter. For travel in both directions, propagation distance was associated with decrease in amplitude and increase in dispersion. Importantly, characteristics of these changes shifted abruptly at various positions along the cord. Discussion: ECAP dispersion increases with propagation distance due to the contribution of slow‐conducting small‐diameter fibers as the signal propagates away from the source. An analysis of the discontinuities in ECAP dispersion changes with propagation revealed that these are due to the termination of smaller‐diameter, slower‐conducting fibers at corresponding segmental levels. The implications regarding SCS lead placement, toward the goal of maximizing clinical benefit while minimizing side‐effects, are discussed. Conflict of Interest: John Parker is the founder and CEO of Saluda Medical and holds stock options. Milan Obradovic, Nastaran Hesam Shariati, Dean M. Karantonis, Peter Single, James Laird‐Wah, Robert Gorman and Mark Bickerstaff are employees of Saluda Medical with stock options. At the time the data was collected for the study, Prof. Cousins was a paid consultant for Saluda Medical. John Parker, Milan Obradovic, Dean Karantonis, James Laird‐Wah, Robert Gorman and Peter Single are co‐inventors in one or more patents related to the topics discussed in this work.